Principles of management: text and cases - Bhattacharyya, Dipak Kumar (Pearson, 2012)
Principles of management: text and cases / Bhattacharyya, Dipak Kumar. -- Delhi: Pearson, 2012 658.4 B575 No. of Copies : 1